2018
DOI: 10.1073/pnas.1803283115
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of polycistronic mRNAs by the endoribonuclease RNase Y and its associated Y-complex inBacillus subtilis

Abstract: Endonucleolytic cleavage within polycistronic mRNAs can lead to differential stability, and thus discordant abundance, among cotranscribed genes. RNase Y, the major endonuclease for mRNA decay in , was originally identified for its cleavage activity toward the operon, an event that differentiates the synthesis of a glycolytic enzyme from its transcriptional regulator. A three-protein Y-complex (YlbF, YmcA, and YaaT) was recently identified as also being required for this cleavage in vivo, raising the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
101
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(124 citation statements)
references
References 53 publications
(84 reference statements)
8
101
1
Order By: Relevance
“…Although previous studies showed that RNase Y is sensitive to secondary structures located downstream of the processing events [10,12], a recent transcriptomic analysis in B. subtilis did not identify any consensus motif (neither sequence nor RNA structure) in proximity of RNase Y cleavages [39]. Our mutational study indicates that the sequence requirement ( i.e .…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Although previous studies showed that RNase Y is sensitive to secondary structures located downstream of the processing events [10,12], a recent transcriptomic analysis in B. subtilis did not identify any consensus motif (neither sequence nor RNA structure) in proximity of RNase Y cleavages [39]. Our mutational study indicates that the sequence requirement ( i.e .…”
Section: Discussioncontrasting
confidence: 58%
“…It has recently been shown that the processing by RNase Y of specific mRNA targets in B. subtilis depends on the so-called Y-complex, composed of RNase Y and interacting proteins [39,40]. Overall, the exact requirements for RNase Y activity in vivo still need to be determined, and current knowledge indicates that this enzyme may exhibit various characteristics in different bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it indicates that in B. subtilis , serine biosynthesis is regulated in an unusual manner relative to biosynthesis of other amino acids. Decrease in serA expression upon entry into stationary phase in B. subtilis was also confirmed by RNA-seq in a recent study [(47) and DeLoughery A, personal communications].…”
Section: Resultssupporting
confidence: 57%
“…This result contradicted the upshift of the msmE transcription reported by Nicolas et al (19). Perhaps, another mechanism, such as mRNA endonucleolytic cleavage, as observed in the regulation of the cggR-gapA operon, is involved (22,23). In contrast to P msmE , melibiose and raffinose strongly induced P msmR activity in the wild-type strain, while stachyose had no effect on P msmR activity compared to the uninduced control ( Fig.…”
mentioning
confidence: 58%